Scientific and Theoretical Foundations of Teaching Systems - Ilić, Mile Đ.; Jerković, Ljiljana S. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
In the available didactic literature, there has not been an attempt to identify the theoretical foundations of teaching systems. The aim of this paper is to identify and compare the scientific and theoretical foundations of traditional and representative innovative teaching systems. Through meta-theoretical analysis and comparison, it was established that the theoretical foundations of the system of lecturer-centered and lecturer-expository teaching represent the conservative didactic paradigm, characterized by stimulus-response (S-R) learning theories, epistemological theories of education, associative psychology, classical-didactic starting points, and the instructions of Herbert, Comenius, and their followers. The primary outcomes of this approach predominantly consist of memorized, reproductive verbal knowledge. Two key methodological conceptions of the conservative didactic paradigm were identified: dogmatic and explanatory-reproductive. The basis of innovative teaching (problem-based, individualized, project-based, contextual, developmental, receptive, responsible, interactive, computerized, inclusive, etc.) is rooted in the rationalist, constructivist, and phenomenological didactic paradigms. They draw upon contemporary didactic theories, S-O-R theories of learning and creativity, theories of intrinsic motivation, non-violent communication and inclusion, the theory of developing teaching, the theory of confluent education, and emancipatory pedagogical and humanistic-personalistic theories. The outcomes of these innovative approaches include transferable knowledge, productive skills, developed thinking and creative abilities, practical life skills, and competences for lifelong learning. The key methodological concepts of the rationalist, constructivist, and phenomenological didactic paradigms are developmental and person-oriented teaching. The more effective the system of innovative teaching is, the more complex its paradigmatic-didactic and complementary multidisciplinary scientific foundations are. This should be respected in the systematic improvement of teaching and overall educational work, in scientific and research activities, the professional education of future teachers, and the permanent professional development of teachers. The key didactic paradigms and related interdisciplinary and multidisciplinary scientific-theoretical foundations of innovative teaching systems were created by identifying and synthesizing exact, mostly experimental didactic-methodical and pedagogical-psychological scientific research. Such scientific empirical research is based on reliable scientific-theoretical starting points and contributes to the further expansion and deepening of didactic-paradigmatic and related interdisciplinary and multidisciplinary theoretical generalizations, which should be based on reform changes in education, the school system, pedagogical institutions, and the second and third cycles of study programs at teachers’ faculties. This study highlights the pedagogical implications of its findings, particularly in the continuous improvement of teaching quality, enhancement of research concepts, dissemination of teaching systems, and the modernization of curricula at teachers’ faculties.